Monoclonal Antibodies for Treatment of COVID-19: An Updated Review of Current Evidence - Nimesh, Saurabh; Kumari, Pratibha; Kumar, Rohit; Gosiya, Gosiya; Quamuddin, Md.; Ahmad, Md. Iftekhar (Borneo Journal of Pharmacy, 2024)
The emergence of COVID-19 in December 2019 spurred a global effort to develop effective medical interventions. Therapeutic monoclonal antibodies (mAbs) have emerged as a promising strategy to combat the SARS-CoV-2 virus. Several mAbs targeting the receptor-binding domain (RBD) of the SARS-CoV-2 spike protein have received Emergency Use Authorization (EUA) for treating mild to moderate COVID-19. Additionally, human mAbs and hyperimmune plasma derived from recovered COVID-19 patients have been explored as potential therapeutic options. This review delves into the potential of mAbs for the diagnosis and treatment of COVID-19 infection. We discuss the mechanisms of action of mAbs, as well as their advantages and limitations. Furthermore, we explore the ongoing research and development efforts to optimize mAb-based therapies for COVID-19.